Development of Tourism Village Potential in the Perspective of Reinventing Government in Kesiman Kertalangu Village, East Denpasar District, Denpasar City - Ni Wayan Santiasih; Oka Martini (Eduvest - Journal of Universal Studies, 2025)
This study analyzes the development of tourism village potential through the perspective of reinventing government in Kesiman Kertalangu Village, East Denpasar District, Denpasar City. The research aims to determine the application of the principles of reinventing government in the development of tourism villages and identify supporting and inhibiting factors in its implementation. The research method uses a descriptive qualitative approach with in-depth interview techniques, observations, and documentation studies. The research informants include the Village Head, Village Secretary, BUMDES managers, and the community. The results of the study show that of the 10 principles of reinventing government, 9 principles have been well implemented, namely catalytic government, community-owned, competitive, results-oriented, customer-oriented, entrepreneurial, anticipatory, decentralized, and market-oriented. One principle that is not optimal is mission-oriented government because the budget system is still bound by the bureaucracy of the APBDes. Supporting factors include unique natural potential, strong leadership, and village government support. The inhibiting factors are the limitation of professional human resources, budget dependence on village funds, and lack of private investment. This tourist village has succeeded in increasing the village's PAD and creating jobs for the local community.